Prarancangan Pabrik High Fructose Syrup (HFS) dari Tepung Tapioka Kapasitas Produksi 100.000 Ton/Tahun - Nuritasari, Yeny Indra, Eni Budiyati, S.T., M.Eng, Rois Fathoni, S.T. M.Sc. Ph.D (2016)
High Fructose Syrup factory was designed with a capacity of 100,000 tons/year. The raw material used is Tapioca Starch. The factory is planned to set up in areas of Lampung, in 2016 and began operations in 2019. High Fructose Syrup widely used in the food industry, such as candy bars, canning fruits, jelly, industrial manufacturing of ice creams, the drinks industry, cyclamate, saccharin, and the food industry as a substitute for cane sugar (sucrose). High Fructose Syrup is made through a process of hydrolysis using an enzyme catalyst. The enzyme will break down molecules sago starch and convert it into glucose. Then glucose is converted to fructose through isomerization process with a enzyme glukoisomerase at a temperature range of 40-60°C and a pressure of 1 atm in flow stirred tank reactor (RATB). Isomerization 50% will produce 42% fructose syrup. Tapioca Starch feedstock requirements as much 80409.369 tons/year, CaCl2 as much as 25.074 tons/year, α-amylase as much as 52.183 tons/year, Glucoamylase as much as 1,753 tons/year, as many as 3,347 HCl, MgSO4 as much as 12.445, NaOH as much as 0.0016 tons/year, Glukoisomerase 10.241 tons/year, Polystyrenephosponate as much as 0.0048 and 1.6203 polyamine epoxy tons/year. The results of the economic analysis of the design of High Fructose Syrup factory acquired total capital investment (TCI) Rp 808,328,560,707.00 and total costs of production (Production Cost) Rp 1206567763200.00. From the results of feasibility analysis was obtained a return on investment (ROI) before taxes 34.81%, and 24.37% after tax. Pay Out Time (POT) before taxes of 2.23 years and 2.91 years after tax. Break Even Point (BEP) 42.82%, Shut Down Point (SDP) 21.47% and the Discounted Cash Flow (DCF) 32.22%. Based on the evaluation of the above, the High Fructose Syrup factory with a a capacity of 100,000 tons/year is considered feasible founded, because it meets the standard requirements for the establishment of a factory.